PEMERIKSAAN PENUNJANG LIKEN AMILOIDOSIS - Anjayani, Sukma Cukey; Anggeraini, Andi Salsa; Nelly, Nelly; Faidah, Nur (Al-Iqra Medical Journal : Jurnal Berkala Ilmiah Kedokteran, 2023)
Lichen amyloidosis (LA) is a disease caused by amyloid deposits in the dermis which is chronic, localized and very itchy. LA is characterized by the presence of discretely scattered hyperpigmented and hyperkeratotic papules, which can coalesce to form verrucous plaques, present in the extensor area of the arms and legs. The pathogenesis of LA is unclear, but suspected that there is reactivity between antikeratin antibodies and amyloid deposits in the skin. Several examination that can be used to make diagnose LA, such as histopathology (hematoxylin-eosin staining and congo-red) and immunofluorescence (IgM, C3, IgA deposits in the basement membrane area). This paper will discuss further about several examinations that can be used to the diagnosis of LA.